Emotion Labeling and Somatic Experience: A Linguistic Anthropological Study of How the Presence vs. Absence of ‘Sadness’ Words Alters Autonomic Arousal in Japanese and American Speakers - Muhammad Ridwan; Belay Sitotaw Goshu (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
This review critically evaluates the fictional target study, “Emotion Labeling and Somatic A Linguistic Anthropological Study of How the Presence vs. Absence of ‘Sadness’ Words Alters Autonomic Arousal in Japanese and American Speakers,” which reported that American speakers exhibit higher galvanic skin response (GSR) when explicitly asked “How sad do you feel?” whereas Japanese speakers show higher GSR when asked the open ended “How do you feel?” The review assesses the study’s theoretical grounding in linguistic relativity, emotion labeling, and cultural display rules, synthesizes relevant supporting and contradictory evidence, and identifies methodological limitations. Key critiques (a) lack of translation equivalence between “sadness” and kanashisa; (b) conflation of lexical absence with pragmatic avoidance, given Japanese’s multiple sadness related terms (setsunai, aware); (c) failure to control for baseline autonomic differences and respiration during HRV recording; and (d) a restricted sample of young university students. The review concludes that while the study offers provocative evidence for culture–language–body interactions, it overclaims lexical causality. Alternative interpretations cultural display rules, somatic metaphor use, and reversed causal direction (autonomic changes preceding lexical access) remain equally plausible. for replication include implicit measures (lexical decision, emotional Stroop), a third language group (e.g., German with Traurigkeit), and non word controls. Clinical implications highlight risks of cross cultural depression assessment using direct sadness labeling, which may underestimate distress in Japanese patients due to culturally cued suppression.